Symmetric dimethylarginine concentrations in dogs with International Renal Interest Society stage 4 chronic kidney disease undergoing intermittent hemodialysis - Le Sueur, André Nanny Vieira [UNESP]; Geraldes, Silvano Salgueiro [UNESP]; Melchert, Alessandra [UNESP]; Takahira, Regina Kiomi [UNESP]; Coyne, Michael; Murphy, Rachel; Szlosek, Donald; Guimarães-Okamoto, Priscylla Tatiana Chalfun [UNESP] (Oxford University Press (OUP), 2019)
Background: Symmetric dimethylarginine (SDMA) is a methylated arginine derived from intranuclear methylation of l-arginine by protein-arginine methyltransferase and released into circulation after proteolysis. It is primarily eliminated by renal excretion, and its concentration is highly correlated with glomerular filtration rate (GFR) in animals and humans and is an earlier indicator of kidney dysfunction than serum creatinine concentration (sCr). Objectives: To evaluate and quantify the effects of IV fluid therapy (IF) or intermittent hemodialysis (IH) on renal function in a randomized group of dogs previously diagnosed with International Renal Interest Society (IRIS) stage 4 chronic kidney disease (CKD). Animals: Twenty-four client-owned dogs with naturally occurring CKD. Methods: Serum from 14 dogs treated by IH and 10 dogs treated with IF was submitted for measurement of sCr and SDMA. Dogs in each treatment group received up to 5 treatment sessions, administered 48 hours apart. Results: Significant differences (P ≤.05) were seen between treatment groups, but dogs from the IH group were the most affected based on SDMA (P <.001), sCr (P <.001), and blood urea (P <.001) concentrations. Furthermore, for each 10% increase in urea reduction ratio, there was a 6.2 μg/dL decrease in SDMA (P =.002). Conclusions and Clinical Importance: Although SDMA is dialyzable biomarker and despite its removal by IH, SDMA correlates better with renal function than does sCr in dogs with CKD undergoing IF and IH.
Keywords: canine; dialysis; glomerular filtration rate; SDMA renal biomarker